Co-Formulation of Iron Oxide and PLGA Nanoparticles to Deliver Curcumin and IFNα for Synergistic Anticancer Activity in A375 Melanoma Skin Cancer Cells - Magdi Abobaker; Mershen Govender; Yahya E. Choonara (Pharmaceutics)
Background/Objectives: Skin cancer remains a significant global health issue, driving the development of new treatment strategies to improve clinical outcomes and prevent recurrence. Traditional monotherapies often face obstacles such as bioactive resistance, prompting interest in combination therapies that enhance efficacy, while minimizing side effects. This study investigated the use of a co-nanoparticle approach of iron oxide nanoparticles (NPs) surface-functionalized with curcumin (Cur-FeONPs) delivered with prolonged-release interferon alpha (IFNα)-loaded PLGA NPs (IFNα-PLGANPs) for the synergistic treatment of malignant melanoma tested in A375 cells. Methods: Extensive in vitro characterization studies of the Cur-FeONPs and IFNα-PLGANPs were performed, including zeta-size profiling, morphological studies, and structural validation, in addition to cytotoxicity assessments on A375 melanoma and NIH-3T3 fibroblast cells. Results: The Cur-FeONP and IFNα-PLGANPs synthesis processes yielded NPs with an average size of 111.0 nm and 97.0 nm, respectively. Morphological and structural validation studies determined the successful synthesis of the nanoparticulate systems, with cell viability analyses displaying significant cytotoxicity against A375 melanoma cells for the combination treatment, when compared to the individual platforms, with a minimal effect on NIH-3T3 fibroblast cells. Conclusions: The results of this study present a promising synergistic approach for enhanced anticancer activity in A375 melanoma skin cancer cells, providing a potential platform for future preclinical and clinical studies.